Age and sex-mediated differences in six-month outcomes after mild traumatic brain injury in young adults: a TRACK-TBI study. (3rd July 2019) - Yue, John K.; Levin, Harvey S.; Suen, Catherine G.; Morrissey, Molly Rose; Runyon, Sarah J.; Winkler, Ethan A.; Puffer, Ross C.; Deng, Hansen; Robinson, Caitlin K.; Rick, Jonathan W.; Phelps, Ryan R. L.; Sharma, Sourabh; et al.
ABSTRACT: Introduction : Risk factors for young adults with mTBI are not well understood. Improved understanding of age and sex as risk factors for impaired six-month outcomes in young adults is needed. Methods : Young adult mTBI subjects aged 18–39 years (18-29y; 30-39y) with six-month outcomes were extracted from the Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot (TRACK-TBI Pilot) study. Multivariable regressions were performed for outcomes with age, sex, and the interaction factor age-group*sex as variables of interest, controlling for demographic and injury variables. Mean-differences ( B ) and 95% CIs are reported. Results : One hundred mTBI subjects (18-29y, 70%; 30-39y, 30%; male, 71%; female, 29%) met inclusion criteria. On multivariable analysis, age-group*sex was associated with six-month post-traumatic stress disorder (PTSD; PTSD Checklist-Civilian version); compared with female 30-39y, female 18-29y ( B = −19.55 [−26.54, −4.45]), male 18-29y ( B = −19.70 [−30.07, −9.33]), and male 30-39y ( B = −15.49 [−26.54, −4.45]) were associated with decreased PTSD symptomatology. Female sex was associated with decreased six-month functional outcome (Glasgow Outcome Scale-Extended (GOSE): B = −0.6 [1.0, −0.1]). Comparatively, 30-39y scored higher on six-month nonverbal processing speed (Wechsler Adult Intelligence Scale-Processing Speed Index (WAIS-PSI); B = 11.88, 95% CI [1.66, 22.09]). Conclusions : Following mTBI, young adults aged 18-29y and 30-39y may have different risks for impairment. Sex may interact with age for PTSD symptomatology, with females 30-39y at highest risk. These results may be attributable to cortical maturation, biological response, social modifiers, and/or differential self-report. Confirmation in larger samples is needed; however, prevention and rehabilitation/counseling strategies after mTBI should likely be tailored for age and sex. Trial registration: ClinicalTrials.gov identifier: NCT01565551.